2006
DOI: 10.4321/s0365-66912006001100005
|View full text |Cite
|
Sign up to set email alerts
|

IGF-I, VEGF y bFGF, como factores pronósticos de la aparición de la retinopatía de la prematuridad

Abstract: Cytokine serum levels in premature infants can be useful as an indicator in ROP screening, as well as being used to predict the probability of suffering the illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 16 publications
0
11
0
2
Order By: Relevance
“…Studies have shown that low serum IGF‐1 is associated with development of severe ROP 48, 49, 50. IGF‐1 supplementation may be a treatment option to prevent the occlusion of vasculature during the first phase of ROP.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that low serum IGF‐1 is associated with development of severe ROP 48, 49, 50. IGF‐1 supplementation may be a treatment option to prevent the occlusion of vasculature during the first phase of ROP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to post-menstrual age at birth and low birth weight, studies have shown that low IGF serum levels can be used as a screening factor for predicting ROP (Hellstrom et al . 2003; Villegas-Becerril et al . 2006).…”
Section: Retinopathy Of Prematuritymentioning
confidence: 99%
“…Una infranutrición proteica determina unos bajos niveles de IGF-1 en suero y eleva el riesgo de ROP (40)(41)(42). La IGF-1 es un factor protector y predictor del desarrollo de ROP (43). Cuando los niveles del IGF-1 y VEGF ascienden comienza de nuevo el desarrollo vascular en la ROP (38).…”
Section: Discussionunclassified
“…Cuando los niveles del IGF-1 y VEGF ascienden comienza de nuevo el desarrollo vascular en la ROP (38). Por ello, mejorar la nutrición y restaurar los niveles de IGF-1 a aquellos encontrados en el útero a través de la nutrición, o conseguir valores en suero similares a los prematuros sin retinopatía puede ayudar a prevenir la ROP (43,44). Al nacimiento, el peso del prematuro y valor de la IGF-1 presentan una fuerte correlación (39).…”
Section: Discussionunclassified